2017
DOI: 10.1097/brs.0000000000001925
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Outpatient Anterior Cervical Surgery

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Similarly, several groups have created protocols and discharge criteria for outpatient surgery. 15,18,25,31 This includes the empowerment of anesthesia colleagues and nursing staff to improve efficiency and implement safety checkpoints. 41 Furthermore, the utilization of a next-day clinic visit or follow-up telephone call can maintain patient satisfaction as well as preserve safety and outcomes.…”
Section: Patient Selection and Discharge Criteriamentioning
confidence: 99%
“…Similarly, several groups have created protocols and discharge criteria for outpatient surgery. 15,18,25,31 This includes the empowerment of anesthesia colleagues and nursing staff to improve efficiency and implement safety checkpoints. 41 Furthermore, the utilization of a next-day clinic visit or follow-up telephone call can maintain patient satisfaction as well as preserve safety and outcomes.…”
Section: Patient Selection and Discharge Criteriamentioning
confidence: 99%
“…It is believed that strict patient selection is important to optimize outcomes and safety of outpatient spine surgeries. [22][23][24][25] However, despite this consensus, currently, there is no evidence-based guideline to help with patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Except for surgical technique, anesthesiology, and patient selection, discharge criteria also could not be neglected. Mohandas et al 23 suggested that patients underwent outpatient cervical spine surgery should be evaluated with a discharge checklist or scale to determine if they can be safely discharged. However, in the included studies, only Chin et al 17 reported the discharge recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of recent retrospective database analyses suggest that successful outpatient anterior cervical fusions can be done without an increased risk of complications 6–8. The surge of outpatient spine surgery, particularly in the USA, is also evident in the recent US-based clinical practice guidelines that advocate early discharge over inpatient care 9…”
Section: Introductionmentioning
confidence: 99%